Preservation of prawns in ice and the assessment of their quality by objective standards - Velankar, N K; Govindan, T K (Indian Journal of Fisheries, 2016)
Prawns and other crustaceans contribute about 15% of the total marine fish landings in India. Our present annual production of prawns is over 100,000 tons, ranking next only to that of the U.S.A. Large quantities of prawns are preserved by sundrying after previously boiling in salt solution for the internal market as well as for export to Ceylon, Burma and Malaya. A relatively small fraction is sent in ice to inland towns by rail or other conveyance. In recent years a considerably valuable trade in export of frozen prawns and lobsters to the U.S.A. has developed.